Phenolic-rich extract from Citrus sinensis leaves attenuates diabetic cardiomyopathy in male wistar rats by modulating oxidative stress, hyperlipidemia, and pyroptosis-related gene expression - Jude Akinyelu; Akinwunmi Oluwaseun Adeoye; Abiodun Aladetuyi; Omodele Ibraheem; Adaora Chinemelum Onodugo; Olapade Samuel Akinlolu; John Adeolu Falode; Olabisi Tajudeen Obafemi; Toluwase Hezekiah Fatoki (Food Chemistry Advances)
Diabetic cardiomyopathy (DCM) is a complication that is closely associated with diabetes mellitus. This study aims to evaluate the effects of free phenolic-rich extract from Citrus sinensis leaves (FPCS) on DCM, and investigate the underlying cardioprotective mechanisms in a type 2 diabetes (T2DM) rat model. Male Wistar rats were given 10 % fructose water for two weeks, followed by a single intraperitoneal injection of 45 mg/kg streptozotocin (STZ) to induce T2DM. Diabetic rats were treated with 100 mg/kg of FPCS via oral gavage daily for 21 days. The effects on serum glucose level, insulin level, lipid profile, and cardiac biomarkers were assessed. Additionally, oxidative stress markers, lipid peroxidation, pyroptosis-related gene expression (lnc-MALAT1, NLRP3, CASPASE-1), and levels of inflammatory factors (CASPASE-1, IL-1β, IL-6) in cardiac tissue were evaluated. Results showed that FPCS treatment significantly reduced hyperglycemia and hyperlipidemia, improved insulin resistance, and suppressed cardiac injury markers. Also, FPCS attenuated oxidative stress and lipid peroxidation, downregulated lnc-MALAT1, NLRP3, CASPASE-1 expression, and decreased CASPASE-1, IL-1β, and IL-6 protein levels. The cardioprotective effects of FPCS may be attributed to its phenolic compounds, as determined by HPLC analysis. Overall, FPCS could be a promising candidate for ameliorating or protecting against DCM.